From Genesis to genetics: the case of evolution and creationism - Moore, John Alexander (University of California Press, 2002)
1.When worlds collide --2.Creation according to Genesis --3.Creationists meet Mr. Darwin, 1859 --4.Making the case for evolution --5.Twentieth-century evidence --6.Evolution on trial, 1925 --7.The rise of "creation science", 1963 --8.Where does this leave us?